Techno-Economic Analysis of the Utilization of Sawdust and Coconut Husk Fiber as Raw Materials for the Production of Cement Boards - Risa Meutia Fiana; Deivy Andhika Permata; Muhammad Fikrul Hadi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study evaluates the technical and economic characteristics of cement boards made from sawdust and coconut husk fiber waste using MgCl? as a catalyst. The cement boards were produced using the cold-pressing method with dimensions of 35 cm × 35 cm × 1 cm. The composition of the cement board consists of 25% sawdust, 15% coconut husk fiber, and 60% cement, along with a MgCl? catalyst amounting to 2.5% of the cement weight. Technical testing adheres to SNI 03-2105-2006, and the economic analysis employs the full costing method to calculate the cost of goods sold and the break-even point. Test results indicate that the physical parameters of the cement board—namely density, moisture content, and total expansion—meet the reference limits specified in SNI 03-2105-2006. Mechanically, the modulus of elasticity meets the reference limits in SNI 03-2105-2006, while the modulus of rupture falls below the minimum reference limit. The economic analysis in this study indicates a production cost of Rp10,749.41 per unit and an estimated selling price of Rp14,000.00, with the break-even point reached at sales of 74 units per year. Cement boards made from sawdust and coconut fiber waste have dimensional stability and stiffness that meet standards, but improvements in mechanical strength and interparticle bonding still require optimization in the production process.